2022
DOI: 10.3390/ijerph19127426
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Perspectives on the Implementation of the Second Opinion Directive in Germany—An Exploratory Sequential Mixed-Methods Study

Abstract: A new Second Opinion Directive (SOD) was introduced in Germany in December 2018 for hysterectomy, tonsillotomy, and tonsillectomy to support shared decision making and to avoid unnecessary surgeries. Owing to its recent implementation, evidence and insights regarding outcomes and challenges encountered with the SOD are lacking, notably from the physicians’ perspective. To assess this, we undertook an exploratory sequential mixed-methods design with an initial qualitative phase followed by a quantitative evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 26 publications
0
7
1
3
Order By: Relevance
“…Interestingly, we found some contradictory results in a previous study among physicians [12]. They stated more frequently that they informed about where to nd an SO physician and that the medical records could be taken along.…”
Section: Discussioncontrasting
confidence: 85%
See 4 more Smart Citations
“…Interestingly, we found some contradictory results in a previous study among physicians [12]. They stated more frequently that they informed about where to nd an SO physician and that the medical records could be taken along.…”
Section: Discussioncontrasting
confidence: 85%
“…The main nding is that the SOD does not reach the health care system because physicians do not provide information as intended in the SOD. While physicians are generally positive about the concept of SOs, a previous study demonstrated that the implementation of SOD is associated with a lack of acceptance and challenges in everyday practice [12]. Insu cient implementation could be explained, on the one hand, by the fact that physicians tend to have a negative attitude towards the SOD.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations